2004
DOI: 10.1159/000079699
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Drainage of Simple Cysts of the Kidney: A New Method

Abstract: Objective: The experience of our department on the treatment of solitary simple kidney cysts with continuous percutaneous drainage for 24 h and instillation of pure alcohol as a sclerotic agent is reported. The results are compared with those of previous years when the treatment consisted of percutaneous drainage and injection of pure alcohol. Patients and Methods: During the period 1992–2001, 252 patients (136 male, 116 female; aged 22–74 years) were treated at our department, and all had a solitary kidney cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 5 publications
2
19
0
1
Order By: Relevance
“…There was complete resolution of the cyst in 84% of them. Similar results were reported, at 71–97%, by other authors who used single or multiple injections with or without 24 h continuous cyst drainage before or after ablation [2,4,8,9,11,14]. Early reports showed a high cyst resolution rate after aspiration and one sclerotherapy injection with alcohol [15].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…There was complete resolution of the cyst in 84% of them. Similar results were reported, at 71–97%, by other authors who used single or multiple injections with or without 24 h continuous cyst drainage before or after ablation [2,4,8,9,11,14]. Early reports showed a high cyst resolution rate after aspiration and one sclerotherapy injection with alcohol [15].…”
Section: Discussionsupporting
confidence: 82%
“…We repeated the procedure immediately after draining the alcohol in cysts of moderate size, but repeated it every 24 h two or three times after an initial 24‐h of drainage in patients with large cysts. The efficacy of continuous drainage for 24 h before injection of alcohol was also reported by Touloupidis et al [4].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In our study, six hypertensive patients (46.1%) benefited from treatment with normalization of blood pressure. Similarly, Touloupidis et al found that, of 61 patients with hypertension, 29 had improved blood pressures after sclerotherapy of simple renal cysts [6]. …”
Section: Discussionmentioning
confidence: 99%